Pengaruh debt default dan financial distress terhadap audit report lag pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2017–2021 - Wokas, Imanuel Jefferson Jordan; Wokas, Heince R. N.; Suwetja, I Gede (Yayasan Widyantara Nawasena Raharja, 2024)
The purpose of this study is to determine the effect of debt default and financial distress on audit report lag in manufacturing companies listed in the Indonesia Stock Exchange in period of 2017 to 2021. Debt default is measured using the debt to assets ratio, financial distress is measured by the Altman Z Score that was modified in 1995, and the audit report lag is the difference between the date of the audit report and the company's financial report. The type of this study is quantitative using a sampling technique, namely purposive sampling which gives 35 of manufacturing firms. The results of multiple linear regression show that debt default and financial distress have no effect on audit report lag.